Cyanobacteria Microcystis aeruginosa Contributes to the Severity of Fish Diseases: A Study on Spring Viraemia of Carp - Palikova, Miroslava; Kopp, Radovan; Kohoutek, Jiri; Blaha, Ludek; Mares, Jan; Ondrackova, Petra; Papezikova, Ivana; Minarova, Hana; Pojezdal, Lubomir; Adamovsky, Ondrej (Toxins, 2021)
Fish are exposed to numerous stressors in the environment including pollution, bacterial and viral agents, and toxic substances. Our study with common carps leveraged an integrated approach (i.e., histology, biochemical and hematological measurements, and analytical chemistry) to understand how cyanobacteria interfere with the impact of a model viral agent, Carp sprivivirus (SVCV), on fish. In addition to the specific effects of a single stressor (SVCV or cyanobacteria), the combination of both stressors worsens markers related to the immune system and liver health. Solely combined exposure resulted in the rise in the production of immunoglobulins, changes in glucose and cholesterol levels, and an elevated marker of impaired liver, alanine aminotransferase (ALT). Analytical determination of the cyanobacterial toxin microcystin-LR (MC-LR) and its structurally similar congener MC-RR and their conjugates showed that SVCV affects neither the levels of MC in the liver nor the detoxification capacity of the liver. MC-LR and MC-RR were depurated from liver mostly in the form of cysteine conjugates (MC-LR-Cys, MC-RR-Cys) in comparison to glutathione conjugates (LR-GSH, RR-GSH). Our study brought new evidence that cyanobacteria worsen the effect of viral agents. Such inclusion of multiple stressor concept helps us to understand how and to what extent the relevant environmental stressors co-influence the health of the fish population.
Keywords: Toxicity Tests; Microcystis; nemoci ryb; testy toxicity; spring viraemia of carp; Fish Diseases; kapři; microcystins; cyanobacteria; mikrocystiny; zvířata; Carps; roční období; stupeň závažnosti nemoci; immune system; Seasons; Water Pollutants, Chemical; Severity of Illness Index; conjugates; Animals; Microcystins; chemické látky znečišťující vodu